One-dimensional ultrasound propagation in stratified gas - Sergey LEBLE; Maxim SOLOVCHUK (Archives of Acoustics, 2009)
The system of hydrodynamic-type equations is derived by two-sided distribution function for a stratified gas in gravity field and applied to the problem of ultrasound. The theory is based on the generalized Gross-Jackson kinetic equation, the solution of which is built by means of locally equilibrium distribution function with different local parameters for molecules moving "up" and "down". The problem of propagation of the sound wave from an oscillating plane is explored. The linearized version of the obtained system is studied and compared with other results and experiments for a wide range of Knudsen numbers (Kn). The discrepancy with experiment in attenuation behavior at big Kn range forced us to use generalized kinetic description leading to the Alexeev-Boltzmann equation. Its use essentially improves the results.